Austerity Policies Bad Ideas in Practice (Springer International Publishing, 2018)
This book takes up the problems of social policy, state intervention and support in the hard times of austerity introduced by the Coalition government 2010-15, and continued under the Conservative government today. At a time when the economy is growing and pay levels finally rising, the necessity for more cuts in public expenditure is fiercely contested. The scope of state services, the levels of support for people in need, and the kinds of organizations that will deliver the services, will all be profoundly affected in coming years. The authors and editors assess some of these consequences visible now in the impact that expenditure cuts and reorganization have had on many areas of social policy, and explore the direction of change in the near future. Austerity Policies evaluates a wide range changing forms of state services and the transformations involving both the recipients and those delivering the services. It considers the past, present and future of austerity as a policy, and the problems affecting particular groups such as offenders, looked after children, and professionals such as social care workers and those engaged with domestic violence. The collection will be of interest to students and scholars of social policy, criminology, sociology, politics and media studies. .